Monocyte IL-10 produced in response to lipopolysaccharide modulates thrombin generation by inhibiting tissue factor expression and release of active tissue factor-bound microparticles - Poitevin, Stéphane; Cochery-Nouvellon, Eva; Dupont, Annick; Nguyen, Philippe (Thrombosis and Haemostasis, 2007)
Lipopolysaccharide (LPS)-stimulated monocytes are known to have a procoagulant effect. This property is currently explained by the fact that monocytes, in response to LPS, can express tissue factor (TF) and undergo a process of membrane microvesiculation. Interleukin-10 (IL-10) has been shown to downregulate TF expression and inhibit procoagulant activity (PCA). In order to further characterize the inhibitory effect of IL-10 on LPS-induced PCA, we used the integrated system of analysis of kinetics of thrombin generation in normal plasma (thrombinography). For this, we developed an original method of elutriation allowing to obtain a highly purified monocyte preparation, under endotoxin-free conditions. Thrombin generation was measured using a highly sensitive and specific fluorogenic method which we adapted to inhibit the contact factor pathway. Results show that recombinant human IL-10 decreased the kinetics of thrombin generation in a dose-dependent manner. Furthermore, the inhibition of endogenous IL-10 released by monocytes in response to LPS is associated with an increase in the kinetics of thrombin generation. We demonstrated that this effect was a consequence of the up-regulation of TF expression and TF-bound microparticle release. In conclusion, we report that IL-10 can regulate thrombin generation in conditions close to physiology as allowed by thrombinography, and that endogenous IL-10 regulates TF expression and release of active TF-bound microparticles by a negative feed back loop through IL-10 receptor α
Keywords: microparticles; Interleukin-10; monocytes; thrombin generation; tissue factor